Oral microbiome and peri-implant diseases: where are we now? - Pokrowiecki R; Mielczarek A; Zaręba T; Tyski S (Dove Medical Press, 2017)
Rafal Pokrowiecki,1 Agnieszka Mielczarek,2 Tomasz Zareba,3 Stefan Tyski3,4 1Department of Head and Neck Surgery-Maxillofacial Surgery, Otolaryngology and Ophthalmology, Prof Stanislaw Popowski Voivoid Children Hospital, Olsztyn, 2Department of Conservative Dentistry, Medical University of Warsaw, 3Department of Antibiotics and Microbiology, National Medicines Institute, 4Department of Pharmaceutical Microbiology, Medical University of Warsaw, Warsaw, Poland Abstract: Peri-implant infective diseases (PIIDs) in oral implantology are commonly known as peri-implant mucositis (PIM) and periimplantitis (PI). While PIM is restricted to the peri-implant mucosa and is reversible, PI also affects implant-supporting bone and, therefore, is very difficult to eradicate. PIIDs in clinical outcome may resemble gingivitis and periodontitis, as they share similar risk factors. However, recent study in the field of proteomics and other molecular studies indicate that PIIDs exhibit significant differences when compared to periodontal diseases. This review aims to elucidate the current knowledge of PIIDs, their etiopathology and diversified microbiology as well as the role of molecular studies, which may be a key to personalized diagnostic and treatment protocols of peri-implant infections in the near future. Keywords: dental plaque, infection, titanium, microbiome, periimplantitis